Increasing knowledge and community attitude in doing Swamedication through extension - Wiryanto, Wiryanto; Reveny, Julia; Tanuwijaya, Juanita; Suwarso, Edy; Surjanto, Surjanto (Talenta Publisher, 2019)
Based on various field studies it is known that many members of the community still lack sufficient knowledge and attitudes to carry out swamedications. Self-medication or self-medication is defined as the use of drugs without professional supervision, to treat health problems with symptoms that are self-identified, recurrent illnesses or minor health problems. Community service is aimed at increasing public knowledge and attitudes about self -ication through counseling. Counseling is addressed to administrators, employees, teachers, and students of the Al Razi Sinar Harapan Education Foundation, having its address at Jl. Eka Rasmi, Melinjo I No. 19 Medan. The counseling activities involved 50 participants, starting with the provision of knowledge materials and attitudes about self-medication, demonstration of various markings on pharmaceutical preparations, introduction of pharmacist figures as community guides in various drug-related problems and their proper use, closed with a question and answer session with prizes. To find out the benefits of counseling in increasing knowledge and attitudes about self-medication, before and after counseling, participants were asked to fill out a questionnaire. Based on the evaluation of filling out the questionnaire before and after counseling, it is known that in general there was an increase in the average points (criteria) of knowledge and attitudes from the previous 44.71 and 41.76 (less) to 56.47 and 52.94 (enough). In more detail, the increase in the mean points (criteria) of knowledge and attitudes of the foundation management group and teachers increased from points 57.14 and 40 (less) to 77.14 (good) and 62.86 (sufficient). From the group of high school students increased from 31.11 and 42.22 points (less) to 60.00 and 64.44 (enough). And from the group of junior high school students increased from 44.71 and 41.76 points (less) to 56.47 and 52.94 (enough). From the results of the evaluation it can be concluded that the extension activities are proven to be able to increase the knowledge and attitudes of the community in conducting self-authentication.